Influencia de "El Niño 1997-98" sobre la fecundidad de Emerita analoga en Lambayeque - Perú - Alvitres, Víctor (1999)
Emerita analoga, an Anomura marine benthíc crab of the Peruvian coast macrozoobenthos is one of the organisms that the RIBEN monitors to determine the influence of "El Niño" events. Sampling was carried out biweekly in San Jose beach (Lambayeque) from April 1996 to July 1998. Cephalotoraxic length (Lc mm) and total weight (g) was registered. The ovigera mass was weighed, and a portion of 0,05 g was used for eggs and breeding count to estimate fertility and contribution of breeding. The data were processed statistically comparing the individuals of April 96 -March 97 with those of April 97 July 98 ("El Niño 1997-98"). The fertility of ovigera females in stadium Ov-1 range from 983 to 17517 (mean 5782), and from 1100 to 18210 (mean 8534) eggs, for the periods April 96-Mareh 97, and "El Niño", respectively. This significant difference was also evident tor Ov-2; however, in relation to the sizes in which fertility increase with the increment of Lc, "El Niño 1997-98" had a negative effect. The fertility - Lc regressíons were different, being the fertility of E. anafoga affected negatively by the "El Niño 1997-98"; in a same way, it influenced negatively in its condition (weight-Iength). "El Niño 1997-98" affected the given breeding positively; because during the pick of this event E. analoga presented another reproductive period that has allowed a good recruitment and the recovering of the population that had disappeared.